Peacekeeping as a Tool of Foreign Policy - Ruggeri, A; Meiske, M (Oxford University Press, 2017)
Peacekeeping is one of the principal activities and foreign policy tools implemented by the international community to create and “maintain international peace and security.” Peacekeeping operations have grown in size and scope since the late 1980s and have included traditional peacekeeping, multidimensional peacekeeping, and peace enforcement. Peacekeeping operations pursue far-reaching objectives ranging from humanitarian assistance and the repatriation of refugees, over the disarmament, demobilization, and reintegration of former combatants, to liberal democratic assistance policies. The proliferation and increased scope of peacekeeping operations imply greater significance of peacekeeping as a tool of foreign policy. As such, peacekeeping operations are not deployed solely according to matters of global peace and security, but the deployment of and contribution to peacekeeping operations is increasingly shaped by individual state’s foreign and security policy considerations. An increasing literature studying the supply side of peacekeeping offers a broad range of arguments for why countries contribute to peacekeeping operations referring to realism, liberalism, alliance politics, or domestic politics. Foreign and security policy goals that states try to attain by participating in peacekeeping operations include status enhancement and influence in the international system, the reduction of the threat of conflict diffusion into its own territory and of a potential influx of refugees, or the stabilization of political relations, international trade, and alliance politics. The existing literature leaves some lingering questions and methodological challenges that require further attention. Of particular importance are questions related to the politics of tool choice and the effectiveness of peacekeeping as a tool of foreign policy. Methodological challenges exist regarding data availability and collection as well as the appropriate modelling of cooperation between different organizations conducting peacekeeping operations and the interdependence of countries’ decisions regarding their choice of peacekeeping as a tool of foreign policy.